Preparation method of rare earth-based luminescent ceramic tile and ceramic tile thereof

CN122897671APending Publication Date: 2026-10-13QINGYUAN GANI CERAMICS CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611314992.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本发明的目的是提供一种稀土基蓄光陶瓷砖的制备方法及其陶瓷砖,旨在解决难以兼顾稀土蓄光材料釉面效果呈现和发光性能的问题

Benefits of technology

[0030]低温锌硼基熔块产生的透光性能的提高,一方面能够增加稀土蓄光发光材料的对光能的捕获,提高其利用效率,进而提高稀土蓄光发光材料的发光强度;同时,由于稀土基蓄光发光材料发光强度的提升,还能够在保持发光性能的情况下减少添加量。当添加量减少,一方面降低生产成本,另一方面还能减少由于“稀土基蓄光发光材料”的添加过多对釉面质感产生的不利影响。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897671A_ABST
    Figure CN122897671A_ABST
Patent Text Reader

Abstract

The present application relates to the field of functional ceramics, in particular to the field of photoluminescence ceramics, especially the field of rare earth-based phosphor ceramics, and discloses a preparation method of rare earth-based phosphor ceramic tiles and the ceramic tiles. The preparation method of the rare earth-based phosphor ceramic tiles comprises the following steps: S1: preparing a ceramic body; S2: drying and then first firing; S3: applying a rare earth-based phosphor glaze on the ceramic body to form a phosphor glaze layer; S4: applying a protective glaze on the phosphor glaze layer; S5: drying and then second firing; in step S4, the formula of the protective glaze comprises protective glaze raw material components 57% to 65% and printing paste 35% to 43% by mass percentage; the protective glaze raw material components comprise low-temperature zinc-boron-based frit 75% to 85% and kaolin 15% to 25%. The rare earth-based phosphor ceramic tile prepared by the present application can maintain the luminescence performance of the rare earth-based phosphor material while not affecting the presentation of the original pattern layer and realizing good texture of the glaze surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional ceramics, particularly to the field of photoluminescent ceramics, and especially to the field of rare earth-based phosphorescent ceramics. Background Technology

[0002] Photoluminescent materials, also known as long-afterglow photoluminescent materials, can absorb and store external light energy and continuously release visible light after the light source is removed. They offer advantages such as requiring no power supply, long afterglow, and energy efficiency, and have been widely used in emergency signage, traffic safety, and architectural decoration. Combining them with ceramic tiles, slabs, and other building ceramic substrates allows for an organic integration of daytime decorative textures and nighttime luminescence, aligning with the trend of personalized, artistic, and functional building decoration materials. However, existing photoluminescent ceramic products still face technical limitations in material composite methods, decorative effects, pattern control, and firing processes, making it difficult to simultaneously meet the comprehensive requirements of artistic expression, surface texture, and luminescent performance.

[0003] At the structural level of the luminescent layer, existing products generally employ methods of layering, filling, or locally stacking luminescent layers, with a thickness often reaching 3–6 mm, and mostly relying on low-temperature curing or low-temperature firing processes. This thick stacking not only makes the decorative surface appear heavy and lacking in depth, but also severely obscures or alters the original texture, color, and feel of the ceramic glaze, resulting in a monotonous daytime visual effect that is difficult to coordinate with complex decorative styles such as marble textures, natural stone, or oil painting patterns. Furthermore, the light storage and luminous intensity are basically equal in each area, resulting in uniform overall luminescence. This lack of variation in light and shadow, gradation, and other elements necessary for artistic expression makes it impossible to simulate the spatial depth of artistic patterns, severely limiting its application in interior art decoration, landscape decoration, and high-end customization. Furthermore, some solutions employ shallow dry application, organic binder composites, or organic material coatings, but these introduce new problems. Specifically, the phosphorescent powder is prone to agglomeration in the binder, resulting in uneven distribution of the luminescent layer and limiting the fineness of the pattern. It also induces defects such as pinholes, bubbles, depressions, glaze shrinkage, and even cracks on the glaze surface, making it difficult to stably control the firing process and adversely affecting the decorative effect of the glaze.

[0004] Therefore, the main technical challenge currently facing the development of glaze formulations is how to ensure that the luminescence performance of rare earth-based phosphorescent materials is maintained without affecting the presentation of the original pattern layer and achieving a good glaze texture. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing rare earth-based phosphorescent ceramic bricks and the ceramic bricks thereof, aiming to solve the problem of difficulty in simultaneously achieving the glaze effect and luminescence performance of rare earth phosphorescent materials.

[0006] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing rare-earth-based photoluminescent ceramic bricks, comprising the following steps: S1: Preparation of ceramic green body; S2: Drying, followed by the first firing; S3: Apply rare earth-based phosphorescent glaze to the ceramic body to form a luminescent glaze layer; S4: Apply a protective glaze to the luminescent glaze layer; S5: Dry, then fire a second time; In step S2, the first firing is a high-temperature firing to form a basic green body structure, which enables the second firing in step S5 to use a medium-low temperature firing temperature to form the green body foundation. This prevents the problem of incomplete melting of the green body during sintering due to the lower tolerance temperature of rare earth-based luminescent materials in the direct one-time firing process, which would lead to a decrease in properties such as density, strength, and porosity.

[0007] In step S3, the rare earth-based phosphorescent glaze includes a protective glaze, a rare earth-based phosphorescent material, and printing ink. Rare earth-based photoluminescent materials include SrAl2O4:Eu 2+ ,Dy 3+ SrAl4O7:Eu 2+ ,Dy 3+ MgSr2Si2O7:Eu 2+ ,Dy 3+ and CaAl2O4:Eu 2+ , Nd 3+ ,La 3+ Any one of them.

[0008] It should be noted that the following formulas are the respective proportions of the four rare earth-based phosphorescent glazes. Any one, two, three, or four of these rare earth-based phosphorescent glazes can be applied to the ceramic body. There is no restriction that only one rare earth-based phosphorescent glaze can be applied to the ceramic body.

[0009] When the rare earth-based photoluminescent material is SrAl2O4:Eu 2+ ,Dy 3+ At that time, by mass percentage, the rare earth-based phosphorescent glaze includes: 77%~85% protective glaze, SrAl2O4:Eu 2+ ,Dy 3+ 10%~15% and printing ink 5%~8%.

[0010] When the rare earth-based photoluminescent material is SrAl4O7:Eu 2+ ,Dy 3+ At that time, by mass percentage, the rare earth-based phosphorescent glaze includes: 80%~85% protective glaze, SrAl4O7:Eu 2+ ,Dy 3+10%~12% and printing ink 5%~8%.

[0011] When the rare earth-based photoluminescent material is MgSr2Si2O7:Eu 2+ ,Dy 3+ At that time, by mass percentage, rare earth-based phosphorescent glaze includes: 80%~85% protective glaze, MgSr2Si2O7:Eu 2+ ,Dy 3+ 10%~12% and printing ink 5%~8%.

[0012] When the rare earth-based photoluminescent material is CaAl2O4:Eu 2+ , Nd 3+ ,La 3+ At that time, by mass percentage, the rare earth-based phosphorescent glaze includes: 82%~87% protective glaze, CaAl2O4:Eu 2+ , Nd 3+ ,La 3+ 8%~10% and printing ink 5%~8%.

[0013] When the rare earth-based photoluminescent material is SrAl2O4:Eu 2+ ,Dy 3+ At that time, the color of the rare earth-based phosphorescent glaze was yellow-green.

[0014] When the rare earth-based photoluminescent material is SrAl4O7:Eu 2+ ,Dy 3+ At that time, the color of the rare earth-based phosphorescent glaze was blue-green.

[0015] When the rare earth-based photoluminescent material is MgSr2Si2O7:Eu 2+ ,Dy 3+ At that time, the color of the rare earth-based phosphorescent glaze was sky blue.

[0016] When the rare earth-based photoluminescent material is CaAl2O4:Eu 2+ , Nd 3+ ,La 3+ At that time, the rare earth-based phosphorescent glaze was purple in color.

[0017] Preferably, in step S3, when preparing the rare earth-based phosphorescent glaze, the protective glaze needs to be prepared first and reserved for later use. Then, the rare earth-based phosphorescent material and printing oil are mixed evenly before being mixed with the protective glaze.

[0018] In step S4, the protective glaze formulation, by mass percentage, includes 57% to 65% of the protective glaze raw material components and 35% to 43% of the printing paste; the protective glaze raw material components include 75% to 85% of the low-temperature zinc-boron-based frit and 15% to 25% of the kaolin.

[0019] The amount of ink added is 5% to 8%. Within this range, the rare earth-based phosphorescent material can be completely coated with ink, reducing the weakening of its luminescence performance due to its own agglomeration when exposed to water.

[0020] In rare earth-based phosphorescent glazes, kaolin can increase the suspension of the glaze, making the distribution of rare earth-based phosphorescent materials in the glaze more uniform.

[0021] In step S4, the protective glaze formulation, by mass percentage, includes 57% to 65% of the protective glaze raw material components and 35% to 43% of the printing paste; the protective glaze raw material components include 75% to 85% of the low-temperature zinc-boron-based frit and 15% to 25% of the kaolin.

[0022] In the above-mentioned protective glaze formulation, the use of printing paste is to increase viscosity and utilize its water-based organic carrier properties to modify the rheological properties and printing performance of the glaze, thereby preventing defects such as paste leakage, flow, screen clogging, pattern blurring, and glaze peeling during the screen printing process.

[0023] In step S4, the low-temperature zinc-boron-based frit, by mass percentage, comprises: 46.85% SiO2, 6.98% Al2O3, 0.04% Fe3O4, 0.01% TiO2, 6.45% CaO, 1.56% MgO, 3.51% K2O, 10.35% Na2O, 0.94% P2O5, 4.48% ZnO, 5.96% BaO, 0.01% SrO, 11.94% B2O3, and 0.92% loss on ignition.

[0024] Low-temperature zinc-boron-based frit can reduce the melting temperature of rare-earth-based photoluminescent glazes while improving the overall light transmittance of rare-earth-based photoluminescent glazes.

[0025] In zinc-boron-based low-temperature frits, zinc oxide has a good fluxing effect, while also widening the melting temperature range of the glaze and preventing glaze cracking. However, adding too much can lead to a cloudy and opaque glaze. Zinc oxide can increase the fluidity of the glaze, allowing gas to escape more easily and maintaining the smoothness of the glaze surface.

[0026] Boron trioxide melts very easily in glazes, has a strong fluxing ability, can increase the refractive index of the glaze, improve the gloss of the glaze, and also improve the fluidity and elasticity of the glaze slurry.

[0027] When zinc oxide ≥4% and boron trioxide ≥10% are present in the zinc-boron-based low-temperature molten block, the melting temperature of rare earth-based phosphorescent glaze and protective glaze can be reduced, making it suitable for the maximum firing temperature of 750℃~790℃, while ensuring the glaze texture, light transmittance and luminous intensity at this temperature.

[0028] In addition, kaolin can adjust the suspension of rare earth-based phosphorescent glazes, making the rare earth-based phosphorescent materials evenly distributed; at the same time, it can also adjust the expansion coefficient of rare earth-based phosphorescent glazes and protective glazes, making the surface smooth and crack-free.

[0029] The combination of low-temperature zinc-boron-based frit and kaolin can reduce the melting temperature of rare-earth-based phosphorescent glazes. Furthermore, since the low-temperature zinc-boron-based frit and kaolin are also components of the protective glaze, they can further reduce the melting temperature during the second firing in the protective glaze, thereby improving the luminescent performance of rare-earth-based phosphorescent materials.

[0030] The improved light transmittance of the low-temperature zinc-boron-based frit can, on the one hand, increase the light energy capture of rare-earth phosphorescent materials, improving their utilization efficiency and thus enhancing their luminous intensity. Simultaneously, the increased luminous intensity of rare-earth-based phosphorescent materials allows for a reduction in the amount added while maintaining luminous performance. This reduction lowers production costs and also mitigates the adverse effects of excessive addition of rare-earth-based phosphorescent materials on the glaze texture.

[0031] On the other hand, when rare earth-based photoluminescent glaze is applied over the pattern layer to add brilliance to the pattern, the good light transmittance of the glaze makes the pattern layer clearer and the overall visual effect more beautiful.

[0032] It should be noted that the reduction in the melting temperature of rare earth-based phosphorescent glaze produced by the low-temperature zinc-boron-based frit needs to be limited to a certain range, because when the melting temperature is too low, the glaze may not be able to form a transparent glass phase, which in turn leads to a decrease in transparency.

[0033] Preferably, after step S1, steps S11 and / or S12 are further included. Step S11 includes applying a surface glaze to the ceramic body; step S12 includes applying a pattern to the ceramic body to form a pattern layer.

[0034] The methods of applying patterns include, but are not limited to: applying an inkjet layer to the surface glaze according to a preset decorative pattern, or screen printing a colored glaze onto the inkjet layer according to a preset decorative pattern.

[0035] There are no restrictions on how the pattern layer is formed; it can be formed on the ceramic body.

[0036] Applying rare earth-based photoluminescent glaze on top of the pattern layer allows the pattern to not only present an artistic aesthetic but also have a luminescent effect.

[0037] It should be noted that the rare earth-based phosphorescent glaze in this invention can also be applied to ceramic surfaces without a pre-designed pattern.

[0038] Preferably, in step S3, the rare earth-based phosphorescent glaze is applied by screen printing.

[0039] Screen printing allows for precise design based on a preset pattern, applying rare-earth-based phosphorescent luminescent glaze to areas requiring a luminescent effect. Furthermore, since the rare-earth-based phosphorescent luminescent materials used in this application include yellow-green, blue-green, sky-blue, and purple, rare-earth-based phosphorescent luminescent glazes with colors similar to the preset pattern can be selected and applied to areas covered by the corresponding colors, resulting in a naturally blended artistic effect without affecting the color presentation of the preset pattern.

[0040] In the preset pattern of the pattern layer, for areas with color gradient transitions, an overprinting design method is used during screen printing to make the color fusion and transition more natural; for areas where colors can be separated, different screen printing plates are designed and screen printed with different rare earth-based phosphorescent luminescent glazes to complete the luminescent structure of the preset pattern.

[0041] Preferably, in step S4, the thickness of the protective glaze is: 0.1mm ≤ protective glaze thickness ≤ 0.32mm.

[0042] Because the protective glaze includes a low-temperature zinc-boron-based frit, which can lower the melting temperature, applying the protective glaze to the surface of the rare earth-based phosphorescent glaze can reduce the overall firing temperature of the glaze, thereby protecting the luminescent properties of the rare earth-based phosphorescent material, as well as protecting the luminescent glaze layer and the color of the glaze.

[0043] In step S5, the second firing process includes a heating stage, a holding stage, and a cooling stage. The heating stage includes raising the temperature from room temperature to 230℃~270℃ at a rate of 5~6℃ / min, then raising it to 580℃~620℃ at a rate of 2~3℃ / min, and then raising it to 750℃~790℃ at a rate of 1~2℃ / min. The holding temperature in the holding stage is 750℃~790℃, and the holding time is 8~12 min. The cooling stage includes lowering the temperature from the highest temperature to 580℃~620℃ at a rate of 5~7℃ / min, then lowering it to 180℃~220℃ at a rate of 3~4℃ / min, and finally lowering it to room temperature at a rate of 4~6℃ / min.

[0044] In step S5, the maximum firing temperature ranges from 750℃ to 790℃, and the holding time is 8 to 12 minutes. This temperature and holding time can be adapted to coordinate the melting temperature of rare earth-based phosphorescent glaze and protective glaze, so as to prepare ceramic bricks that take into account both the luminescent performance and surface texture of rare earth phosphorescent materials.

[0045] The present invention also provides a rare earth-based phosphorescent ceramic brick, which is prepared by the above-mentioned method for preparing rare earth-based phosphorescent ceramic brick. Attached Figure Description

[0046] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0047] Figure 1 Example 4: Effect image of rare earth-based phosphorescent ceramic bricks prepared under natural light.

[0048] Figure 2 Example 4: The luminescence effect of the rare earth-based phosphorescent ceramic brick prepared in the dark. Specific Implementation The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of this application can be combined with each other. At the same time, the raw materials mentioned below, unless otherwise specified, are all commercially available products; the process steps or preparation methods not mentioned in detail are all process steps or preparation methods known to those skilled in the art.

[0050] This embodiment provides a rare earth-based phosphorescent ceramic brick, comprising the following steps: S1: Preparation of ceramic green body; S2: Drying, followed by the first firing; S3: Apply rare earth-based phosphorescent glaze to the ceramic body to form a luminescent glaze layer; S4: Apply a protective glaze to the luminescent glaze layer; S5: Dry, then fire a second time; In step S3, the rare earth-based phosphorescent glaze includes a protective glaze, a rare earth-based phosphorescent material, and printing ink. Rare earth-based photoluminescent materials include SrAl2O4:Eu 2+ ,Dy 3+ SrAl4O7:Eu 2+ ,Dy 3+ MgSr2Si2O7:Eu 2+ ,Dy 3+ and CaAl2O4:Eu 2+ , Nd 3+ ,La 3+Any one of them; When the rare earth-based photoluminescent material is SrAl2O4:Eu 2+ ,Dy 3+ At that time, the color of the rare earth-based phosphorescent glaze was yellow-green.

[0051] When the rare earth-based photoluminescent material is SrAl4O7:Eu 2+ ,Dy 3+ At that time, the color of the rare earth-based phosphorescent glaze was blue-green.

[0052] When the rare earth-based photoluminescent material is MgSr2Si2O7:Eu 2+ ,Dy 3+ At that time, the color of the rare earth-based phosphorescent glaze was sky blue.

[0053] When the rare earth-based photoluminescent material is CaAl2O4:Eu 2+ , Nd 3+ ,La 3+ At that time, the rare earth-based phosphorescent glaze was purple in color.

[0054] In step S4, the protective glaze formulation, by mass percentage, includes 57% to 65% of the protective glaze raw material components and 35% to 43% of the printing paste; the protective glaze raw material components include 75% to 85% of the low-temperature zinc-boron-based frit and 15% to 25% of the kaolin.

[0055] In step S4, the low-temperature zinc-boron-based frit, by mass percentage, comprises: 46.85% SiO2, 6.98% Al2O3, 0.04% Fe3O4, 0.01% TiO2, 6.45% CaO, 1.56% MgO, 3.51% K2O, 10.35% Na2O, 0.94% P2O5, 4.48% ZnO, 5.96% BaO, 0.01% SrO, 11.94% B2O3, and 0.92% loss on ignition.

[0056] Preferably, after step S1, steps S11 and / or S12 are further included. Step S11 includes applying a surface glaze to the ceramic body; step S12 includes applying a pattern to the ceramic body to form a pattern layer.

[0057] Methods of applying patterns include: applying an inkjet layer to the surface glaze according to a preset decorative pattern, or screen printing a colored glaze onto the inkjet layer according to a preset decorative pattern.

[0058] There are no specific rules on how the pattern layer is formed; it is sufficient to form the pattern layer on the ceramic body.

[0059] Preferably, in step S3, the rare earth-based phosphorescent glaze is applied by screen printing.

[0060] In the preset pattern of the pattern layer, for areas with color gradient transitions, an overprinting design method is used during screen printing to make the color fusion and transition more natural; for areas where colors can be separated, different screen printing plates are designed and screen printed with different rare earth-based phosphorescent luminescent glazes to complete the luminescent structure of the preset pattern.

[0061] It should be noted that, in the specific embodiment, the four different colors of rare earth-based phosphorescent glazes are prepared separately and printed on the corresponding areas according to the design of the screen printing plate during the screen printing process.

[0062] Preferably, in step S4, the thickness of the protective glaze is: 0.1mm ≤ protective glaze thickness ≤ 0.32mm.

[0063] In step S5, the second firing process includes a heating stage, a holding stage, and a cooling stage. The heating stage includes raising the temperature from room temperature to 230℃~270℃ at a rate of 5~6℃ / min, then raising it to 580℃~620℃ at a rate of 2~3℃ / min, and then raising it to 750℃~790℃ at a rate of 1~2℃ / min. The holding temperature in the holding stage is 750℃~790℃, and the holding time is 8~12 min. The cooling stage includes lowering the temperature from the highest temperature to 580℃~620℃ at a rate of 5~7℃ / min, then lowering it to 180℃~220℃ at a rate of 3~4℃ / min, and finally lowering it to room temperature at a rate of 4~6℃ / min.

[0064] The final product was a rare earth-based phosphorescent ceramic brick.

[0065] The surface of the ceramic tiles was evaluated, and the luminous intensity of the ceramic tiles was tested.

[0066] Surface evaluation includes assessment of surface texture, color presentation, and transparency.

[0067] Among them, the evaluation of color presentation is the color of the pattern layer, because after applying rare earth-based phosphorescent glaze, an inappropriate glaze formula will cover the pattern layer underneath, thus affecting the original color expression of the pattern layer.

[0068] The instrument used to measure luminous intensity is the PR-305 long afterglow meter.

[0069] The testing method is as follows: Before the test, the ceramic tile is placed in a dark environment for 24 hours, and then the sample is irradiated with a D65 standard light source for 60 minutes. During the irradiation, the surface illuminance of the sample is 1000 lx. After the light source is turned off, the surface brightness of the ceramic tile is measured immediately using a PR-305 long afterglow tester, and the brightness of the sample at the moment the light is turned off is recorded.

[0070] Examples 1-1 to Examples 1-6 This series of embodiments provides a rare earth-based phosphorescent ceramic brick, comprising the following steps: S1: Preparation of ceramic green body; The green body composition, by mass percentage, includes: 66.5% SiO2, 21% Al2O3, 0.18% Fe3O4, 0.07% TiO2, 0.8% MgO, 3.3% K2O, 2.7% Na2O, and 5.45% loss on ignition; S11: Apply surface glaze to the ceramic body; S12: Apply patterns to the ceramic body to form a pattern layer; In step S12, the pattern layer is formed using inkjet printing and screen printing. The inkjet printer uses a 6-channel printing method. The inks for each channel are: E3566 diamond blue ink from Botaco Holdings Co., Ltd.; CXN55212 dark brown ink from Toryceps S.A. Co., Ltd.; CXN31799 beige ink from Toryceps S.A. Co., Ltd.; CIKNE6118 black ink from Toryceps S.A. Co., Ltd.; NGY62012 wrapped yellow ink from Foshan Yangzi Pigment Co., Ltd.; and NGY62016 wrapped red ink from Foshan Yangzi Pigment Co., Ltd.

[0071] The screen printing glazes include four types: cobalt blue glaze from Dongguan Xiehe Ceramics Co., Ltd.; chrome green glaze from Foshan Jinweisheng Ceramic Pigment Co., Ltd.; peacock green glaze from Foshan Jinhong Ceramics Co., Ltd.; and vanadium zirconium blue glaze from Jize County Aokun Dye Purchase and Sales Co., Ltd.

[0072] S2: Drying, followed by the first firing; The first firing temperature is 1224℃, and the firing time is 60 minutes. The first firing is intended to vitrify the ceramic body. Taking a commonly known formula for building ceramic brick body as an example, the firing temperature is preferably 1150℃~1250℃. Those skilled in the art can select a suitable firing temperature based on the body formula. S3: Apply rare earth-based phosphorescent glaze to the ceramic body to form a luminescent glaze layer; S4: Apply a protective glaze to the luminescent glaze layer; S5: Dry, then fire a second time.

[0073] In step S3, the rare earth-based phosphorescent glaze includes a protective glaze, a rare earth-based phosphorescent material, and printing ink. The rare earth-based phosphorescent material includes SrAl2O4:Eu 2+ ,Dy 3+ SrAl4O7:Eu 2+ ,Dy 3+ MgSr2Si2O7:Eu2+ ,Dy 3+ and CaAl2O4:Eu 2+ , Nd 3+ ,La 3+ Any one of them.

[0074] In step S3, the screen printing plates and application amounts used in Examples 1-1 to 1-6 are consistent, that is, the area covered by the rare earth-based phosphorescent luminescent glaze of the same color on the body is consistent, the difference lies in the different formulations of the rare earth-based phosphorescent luminescent glaze of the same color.

[0075] Examples 1-1 to 1-6, rare earth-based phosphorescent luminescent glazes, have their proportions and types of rare earth-based phosphorescent materials as shown in Tables 1 to 6 by mass percentage: Table 1 (Example 1-1) Table 2 (Examples 1-2) Table 3 (Examples 1-3) Table 4 (Examples 1-4) Table 5 (Examples 1-5) Table 6 (Examples 1-6) By mass percentage, the formulations of the protective glazes in Examples 1-1 to 1-6 are consistent, all including 60% of the protective glaze raw material components and 40% of the printing paste; the protective glaze raw material components include 80% of the low-temperature zinc-boron-based frit and 20% of the kaolin.

[0076] In step S4, the protective glaze applied in Examples 1-1 to 1-6 consists of two layers, each with a thickness of 0.3 mm.

[0077] By mass percentage, the low-temperature zinc-boron-based frit comprises: SiO2 46.85%, Al2O3 6.98%, Fe3O4 0.04%, TiO2 0.01%, CaO 6.45%, MgO 1.56%, K2O 3.51%, Na2O 10.35%, P2O5 0.94%, ZnO 4.48%, BaO 5.96%, SrO 0.01%, B2O3 11.94%, and a loss on ignition of 0.92%.

[0078] In the schemes of Examples 1-1 to 1-6, the method of applying the pattern includes: firstly, applying an inkjet layer on the surface glaze layer according to a preset decorative pattern, and then using colored glaze to screen print on the inkjet layer according to the preset decorative pattern to form a pattern layer.

[0079] It should be noted that the ceramic tiles in embodiments 1-1 to 1-6 are all prepared based on the same preset decorative pattern. According to the outline of the preset pattern, rare earth-based phosphorescent luminescent glaze of the same color is applied to the same area on the pattern layer. The difference between the embodiments lies in the raw material ratio of the same color rare earth-based phosphorescent luminescent glaze.

[0080] In the preset pattern of the pattern layer, for the transition areas of color gradients, when screen printing, an overprinting design method is used to make the color blending and transition more natural.

[0081] In step S5, the second firing regime of Examples 1-1 to 1-6 remains consistent, all including a heating stage, a holding stage, and a cooling stage. The heating stage includes heating from room temperature to 250°C at 5.6°C / min, then heating to 600°C at 2.5°C / min, and then heating to 750°C at 1.8°C / min. The holding temperature in the holding stage is 750°C, and the holding time is 10 min. The cooling stage includes cooling from the highest temperature to 600°C at 6°C / min, then cooling to 200°C at 3°C / min, and finally cooling to room temperature at 5°C / min.

[0082] The surface texture, color presentation, and transparency of the ceramic tiles were evaluated, and the luminous intensity of the ceramic tiles was tested. The results are shown in Table 7. Table 7 The above results show that the glazes of Examples 1-1 to 1-6 are matte or semi-matte, and the glazes are transparent and do not cover the pattern layer. The rare earth-based phosphorescent glaze and the pattern layer together create the pattern luminescence effect.

[0083] Comparative Examples 1-1 to 1-8 and Examples 2-1 to 2-2 Comparative Examples 1-1 to 1-8 are based on Example 1-1, differing from Example 1-1 in that the type and proportion of frit in the protective glaze raw material components are different. Specifically, in Comparative Examples 1-1 to 1-4, the parameters of both the rare earth-based phosphorescent glaze and the frit applied to it were adjusted; in Comparative Examples 1-5 to 1-8, the frit parameters of only one of the rare earth-based phosphorescent glazes or the protective glaze were adjusted.

[0084] Examples 2-1 and 2-2 are based on Example 1-1, but differ from Example 1-1 in that the proportion of low-temperature zinc-boron-based frit in the raw material components of rare earth-based phosphorescent glaze and protective glaze is different.

[0085] The other frits used in Comparative Examples 1-3 to 1-8 were either 918 frits or 915 frits, both of which were low-temperature frits.

[0086] Based on the mass percentage of oxides, the 918 frit comprises: 55.16% SiO2, 14% Al2O3, 0.02% Fe3O4, 0.01% TiO2, 7.45% CaO, 2.14% MgO, 2.37% K2O, 4% Na2O, 0.94% P2O5, 7.86% BaO, 0.01% SrO, 5.14% B2O3, and a loss on ignition of 0.63%.

[0087] Based on the mass percentage of oxides, the 915 frit comprises: 52.35% SiO2, 9.14% Al2O3, 0.03% Fe3O4, 0.01% TiO2, 14.03% CaO, 2.14% MgO, 2.37% K2O, 2.41% Na2O, 5.31% ZnO, 3.75% BaO, 5.17% B2O3, 2.45% LiO, and a loss on ignition of 0.84%.

[0088] The scheme design for frit addition amount and frit type, expressed as a percentage by mass, is shown in Table 8: Table 8 The surface texture, color presentation, and transparency of the ceramic tiles were evaluated, and the luminous intensity of the ceramic tiles was tested. The results are shown in Table 9. Table 9 In Comparative Examples 1-1, 1-3, and 1-4, the luminescence intensity results are represented by " / ", because their surface texture is substandard and there is no need to test their luminescence intensity. Comparative Example 1-1, without the addition of kaolin, exhibits glaze cracking, but the glaze layer in the uncrackled areas still maintains a certain degree of transparency, indicating that the lack of kaolin causes the glaze expansion coefficient to be inconsistent with the underlying surface glaze layer and pattern layer. The glaze in Comparative Example 1-2 is dull and has a rough feel, indicating that when the amount of low-temperature zinc-boron-based frit added is too low, on the one hand, it cannot lower the overall melting temperature of the rare-earth-based phosphorescent glaze, leading to the loss of luminescence performance; on the other hand, excessive kaolin addition reduces transparency, causing the glaze to turn slightly white and slightly obscuring the original colors of the pattern, thus weakening the color presentation effect.

[0089] In Comparative Examples 1-3 and 1-4, the formulations of the rare-earth-based phosphorescent glaze and the protective glaze applied on it were adjusted. The frits used were 918 and 915 frits, respectively. In Comparative Example 1-3, the frit was 918 frit, which does not contain ZnO and contains only 5.14% B2O3. With a frit content of 80%, a whitish hue appeared, indicating that the 918 frit could not bond well with kaolin to produce a good glaze effect. In Comparative Example 1-4, the frit was 915 frit, which contained 5.31% ZnO and 5.17% B2O3. Although ZnO > 4%, B2O3 < 10%, resulting in pinholes and a small number of bubbles on the glaze surface, indicating that the 915 frit could not bond well with kaolin to produce a good glaze effect.

[0090] In Comparative Examples 1-5 to 1-6, the frit in the rare earth-based phosphorescent glaze was changed to other low-temperature frits, and the protective glaze formula remained the same as in Example 1-1. The results showed that in Comparative Examples 1-5 using 918 frit, the frit in the rare earth-based phosphorescent glaze did not contain zinc oxide, and the boron trioxide content was 5.17%, which was less than 10%. Therefore, the fluidity of the glaze surface was weakened, and it showed obvious graininess. The transparency of the glaze surface also decreased. In Comparative Examples 1-6 using 915 frit, although the frit contained ≥4% zinc oxide, the boron trioxide content was still less than 10%, so more pores appeared.

[0091] In Comparative Examples 1-7 to 1-8, the frit in the protective glaze was changed to other low-temperature frits, and the formulation of the rare earth-based phosphorescent glaze was the same as that in Example 1-1. The results showed that, similar to Comparative Example 1-5, Comparative Examples 1-7 using 918 frit had a "semi-transparent" glaze surface, indicating that the 918 low-temperature frit had a masking effect on the underlying pattern in both the rare earth-based phosphorescent glaze and the protective glaze due to insufficient melting. At the same time, Comparative Examples 1-8 were similar to Comparative Examples 1-6, with a glossy and uneven glaze surface, indicating that when the zinc oxide content in the glaze frit was ≥4% and the boron trioxide content was ≤10%, it could not be compatible with the kaolin in the protective glaze to produce a smooth and dense glaze surface.

[0092] Comparative Example 2 and Example 3 Comparative Example 2 and Example 3 are based on Example 1-1, but differ from Example 1-1 in that the thickness of the applied protective glaze is different, and the thickness is increased by increasing the number of protective glaze layers. The specific layer design is shown in Table 10: Table 10 The surface texture, color presentation, and transparency of the ceramic tiles were evaluated, and the luminous intensity of the ceramic tiles was tested. The results are shown in Table 11. Table 11 The above results indicate that the thicker the protective glaze, the better the protective effect on rare-earth-based phosphorescent materials. Meanwhile, the results of Comparative Example 2 show that without a protective glaze, the glaze surface is dull and opaque, indicating that the protective glaze has a significant protective effect on luminescence performance and glaze surface appearance.

[0093] Comparative Examples 3-1 to 3-2 Comparative Examples 3-1 and 3-2 are based on Example 1-1, except that the percentage of printing ink in the rare earth-based phosphorescent glaze is different. The specific design is shown in Table 12. Table 12 The printability of the prepared rare-earth-based phosphorescent glaze was evaluated, and its viscosity was measured. The results are shown in Table 13. Table 13 Compared with Example 1-1, the results of Comparative Example 3-1 show that when the amount of printing ink added is 0, the rare earth-based phosphorescent glaze quickly adheres and cannot be printed. This is because the rare earth-based phosphorescent material is prone to clumping when exposed to water, and it needs to be coated. The results of Comparative Example 3-2 show that when the amount of printing ink added is 10%, the viscosity value is much lower than 9500 mPa·s in Example 1-1. When screen printing is performed, the screen sticks and cannot be formed on the brick surface, so the glaze cannot be clearly printed.

[0094] Comparative Examples 4-1 to 4-8 Comparative Examples 4-1 to 4-8 are based on Example 1-1, except that the amounts of rare earth-based phosphorescent materials, protective glaze, and printing ink added in the rare earth-based phosphorescent glaze are different.

[0095] The parameter settings for Comparative Examples 4-1 to 4-8 are shown in Tables 14 to 21: Table 14 (Comparative Example 4-1) Table 15 (Comparative Example 4-2) Table 16 (Comparative Example 4-3) Table 17 (Comparative Example 4-4) Table 18 (Comparative Examples 4-5) Table 19 (Comparative Examples 4-6) Table 20 (Comparative Examples 4-7) Table 21 (Comparative Examples 4-8) The surface texture, color presentation, and transparency of the ceramic tiles were evaluated, and the luminous intensity of the ceramic tiles was tested. The results are shown in Table 22. Table 22 Compared to Examples 1-1, the glaze of Comparative Example 4-1 is rough to the touch, indicating that the SrAl2O4:Eu 2+ ,Dy 3+ Adding too much rare-earth phosphorescent material damages the glaze, creating an uneven surface and a whitening effect that obscures the original pattern; (Comparative Example 4-2: SrAl2O4:Eu) 2+ ,Dy 3+ After the addition of rare-earth phosphorescent materials was reduced, the glaze on the areas coated with the corresponding colors produced an oily sheen, and the surface luminescence intensity decreased to 3151 mcd / m². 2 .

[0096] Compared with Example 1-1, the glaze of Comparative Example 4-3 is not transparent, and the rare earth-based phosphorescent material, which originally appeared blue-green, has a certain blue-white feel. At the same time, it has a masking effect on the original color of the pattern layer below. The rare earth-based phosphorescent material added in Comparative Example 4-4 is less, so it does not have a masking effect on the pattern layer below, but the glaze is not smooth.

[0097] The effects of Comparative Examples 4-5 and 4-6 show the same trend as those of Comparative Examples 4-3 and 4-4.

[0098] In Comparative Examples 4-7, the purple rare earth-based phosphorescent materials also exhibited an opaque appearance and a purplish-white hue due to the large amount added; in Comparative Examples 4-8, the rare earth-based phosphorescent materials were added in smaller amounts, and the glaze surface was uneven.

[0099] The above results indicate that rare earth-based phosphorescent materials of different colors need to be coated with protective glazes of different proportions under the coating of printing ink in order to balance the luminescence performance of rare earth-based phosphorescent materials and the glaze effect.

[0100] Comparative Examples 5-1 to 5-2 and Example 4 Comparative Examples 5-1 to 5-2 and Example 4 are based on Examples 1-6, except that the second sintering temperature is different. The specific design parameters are shown in Table 23. Table 23 The rare-earth-based phosphorescent ceramic brick prepared in Example 4 is shown in the image under natural light. Figure 1 As shown.

[0101] The luminescence effect of the rare-earth-based phosphorescent ceramic brick prepared in Example 4 in the dark is shown in the figure below. Figure 2 As shown.

[0102] The surface texture, color presentation, and transparency of the ceramic tiles were evaluated, and the luminous intensity of the ceramic tiles was tested. The results are shown in Table 24. Table 24 Compared to Examples 1-6, Example 4 exhibits a matte finish reminiscent of oil painting, and its luminous intensity reaches 6249 mcd / m². 2 The results show that the glaze effect at the highest firing temperature of 770℃ is better than that at 750℃. The glaze of Comparative Example 5-1, which was fired at 800℃, is uneven, while the glaze of Comparative Example 5-2, which was fired at 700℃, is whitish.

[0103] The above description is merely a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.

Claims

1. A method for preparing a rare earth-based photoluminescent ceramic brick, characterized in that, Includes the following steps: S1: Preparation of ceramic green body; S2: Drying, followed by the first firing; S3: Apply rare earth-based phosphorescent glaze to the ceramic body to form a luminescent glaze layer; S4: Apply a protective glaze to the luminescent glaze layer; S5: Dry, then fire a second time; In step S4, the protective glaze formulation, by mass percentage, comprises 57%–65% protective glaze raw material components and 35%–43% printing paste; the protective glaze raw material components comprise 75%–85% low-temperature zinc-boron-based frit and 15%–25% kaolin. The zinc-boron-based cryogenic melting block, by mass percentage of oxides, contains ≥4% zinc oxide and ≥10% boron trioxide.

2. The preparation method of a rare earth-based photoluminescent ceramic brick as described in claim 1, characterized in that, In step S3, the rare earth-based phosphorescent luminescent glaze includes the protective glaze, the rare earth-based phosphorescent luminescent material, and the printing ink. The rare earth-based photoluminescent material includes SrAl2O4:Eu 2+ ,Dy 3+ SrAl4O7:Eu 2+ ,Dy 3+ MgSr2Si2O7:Eu 2+ ,Dy 3+ and CaAl2O4:Eu 2+ , Nd 3+ ,La 3+ Any one of them.

3. The method for preparing a rare earth-based photoluminescent ceramic brick as described in claim 2, characterized in that, When the rare earth-based photoluminescent material is SrAl2O4:Eu 2+ ,Dy 3+ At that time, by mass percentage, the rare earth-based phosphorescent glaze comprises: 77%~85% of the protective glaze, SrAl2O4:Eu 2+ ,Dy 3+ 10%~15% and printing ink 5%~8%.

4. The preparation method of a rare earth-based photoluminescent ceramic brick as described in claim 2, characterized in that, When the rare earth-based photoluminescent material is SrAl4O7:Eu 2+ ,Dy 3+ At that time, by mass percentage, the rare earth-based phosphorescent glaze comprises: 80%~85% of the protective glaze, SrAl4O7:Eu 2+ ,Dy 3+ 10%~12% and printing ink 5%~8%.

5. The method for preparing a rare earth-based photoluminescent ceramic brick as described in claim 2, characterized in that, When the rare earth-based photoluminescent material is MgSr2Si2O7:Eu 2+ ,Dy 3+ At that time, by mass percentage, the rare earth-based phosphorescent glaze comprises: 80%~85% of the protective glaze, MgSr2Si2O7:Eu 2+ ,Dy 3+ 10%~12% and printing ink 5%~8%.

6. The method for preparing a rare earth-based photoluminescent ceramic brick as described in claim 2, characterized in that, When the rare earth-based photoluminescent material is CaAl2O4:Eu 2+ , Nd 3+ ,La 3+ At that time, by mass percentage, the rare earth-based phosphorescent glaze comprises: 82%~87% of the protective glaze, CaAl2O4:Eu 2+ , Nd 3+ ,La 3+ 8%~10% and printing ink 5%~8%.

7. The preparation method of a rare earth-based photoluminescent ceramic brick as described in claim 1, characterized in that, In step S4, the low-temperature zinc-boron based frit, by mass percentage of oxides, comprises: SiO2 46.85%, Al2O3 6.98%, Fe3O4 0.04%, TiO2 0.01%, CaO 6.45%, MgO 1.56%, K2O 3.51%, Na2O 10.35%, P2O5 0.94%, ZnO 4.48%, BaO 5.96%, SrO 0.01%, B2O3 11.94%, and a loss on ignition of 0.92%.

8. The method for preparing a rare earth-based photoluminescent ceramic brick as described in claim 1, characterized in that, In step S4, the thickness of the protective glaze application is: 0.1mm ≤ protective glaze thickness ≤ 0.32mm.

9. The method for preparing a rare earth-based photoluminescent ceramic brick as described in claim 1, characterized in that, In step S5, the second firing process includes a heating stage, a holding stage, and a cooling stage. The heating stage includes raising the temperature from room temperature to 230℃~270℃ at a rate of 5~6℃ / min, then raising it to 580℃~620℃ at a rate of 2~3℃ / min, and then raising it to 750℃~790℃ at a rate of 1~2℃ / min. The holding temperature in the holding stage is 750℃~790℃, and the holding time is 8~12 min. The cooling stage includes lowering the temperature from the highest temperature to 580℃~620℃ at a rate of 5~7℃ / min, then lowering it to 180℃~220℃ at a rate of 3~4℃ / min, and finally lowering it to room temperature at a rate of 4~6℃ / min.

10. A rare earth-based phosphorescent ceramic brick prepared by the preparation method according to any one of claims 1 to 9.